Efficacy and Antifungal Mechanism of root exudate Kaempferia galanga against Colletotrichum capsici - Andri Purniawan; Suwandi Suwandi; Rahmad Fadli; Berta Apriliani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Colletotrichum capsici causes anthracnose in chili plants, which can drastically impair productivity and fruit quality. Pesticide-based pest control is often ineffective, necessitating a more environmentally friendly option. The purpose of this study is to investigate the suppressive microbiome capability of Kaempferia galanga rhizome exudate in preventing C. capici growth. The microbiome is obtained by enrichment with a pathogenic inoculum and the addition of chitin. In vitro, antifungal activity was assessed by monitoring the percentage of colony inhibition, changes in hyphal shape, and measuring electrical conductivity (EC) as a sign of cell membrane damage. According to research findings, the suppressive microbiome can restrict the establishment of pathogenic colonies while also inducing the creation of chlamydospores in response to stress. The inclusion of chitin resulted in the strongest antifungal activity and elevated the EC value to 320.67 µS cm-1, indicating electrolyte leakage from cell membrane disruption. These findings suggest that the microbiome from K. galanga rhizome exudate has the potential to act as a biological control agent for anthracnose in chili peppers. More research is required to discover the important microorganisms and bioactive chemicals involved in antifungal processes.